The Effectiveness of Educational Punishment in Improving Student Discipline: A Case Study in South Sulawesi - Asmira, Asmira; Herlina, Susi; Mustika, Sri; Sulaeman, Sulaeman (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study investigates the effectiveness of educational punishment in enhancing student discipline within public elementary schools in South Sulawesi, Indonesia. Grounded in qualitative research methodology, the study utilized classroom observation, structured interviews with teachers, and document analysis to assess behavioral changes among students following the implementation of corrective disciplinary measures. The findings reveal a significant improvement in students' adherence to school rules and classroom norms after the introduction of pedagogically sound punishments. The disciplinary interventions were carefully designed to be constructive, non-threatening, and proportional to the students’ infractions. Cooperation between teachers, school principals, and students played a crucial role in supporting the enforcement of discipline. The study concludes that educational punishment, when applied with consistency and empathy, serves not only as a deterrent but also as a developmental tool for shaping responsible student behavior. These findings have implications for educators and policymakers seeking effective, ethical strategies for managing discipline in primary education.